Primary Carbide Formation in Tool Steels: Potential of Selected Laboratory Methods and Potential of Partial Premelting for the Generation of Thermodynamic Data. Issue 4 (29th December 2022) - Presoly, Peter; Gerstl, Bernhard; Bernhard, Christian; Marsoner, Stefan; Angerer, Paul; Friessnegger, Bernhard; Hahn, Susanne
Abstract : To predict the solidification and product properties of tool steels with complex chemical compositions, an understanding of the transformation behavior is crucial. Therefore, the quaternary Fe–C system with 10 wt% Cr and 3 wt% W (a subsystem of cold work steels, with M7 C3 and M23 C6 carbides) and the Fe–C system with 6 wt% W and 5 wt% Mo (simplified high‐speed steel, with M6 C and MC carbides) are selected. The motivation for this study is to develop a methodology for the safe and fast production of model alloys and the close to equilibrium performance of differential scanning calorimetry (DSC) measurements. Regular diffusion annealing of as‐cast carbidic steels is time‐consuming, but with an additional heat treatment during the DSC measurement in the semisolid zone (30–50% liquid phase fraction), a status close to equilibrium can be achieved within minutes due to the high diffusion. To prove the potential of the equilibration by partial premelting in the DSC, additional equilibration and quenching experiments are performed in a Tammann furnace and investigated using a scanning electron microscope and X‐ray diffraction analysis. By combining these methods, carbide types and the transformation temperatures can be verified to evaluate and construct complete phase diagrams. Abstract : The potential of differential scanning calorimetry measurements with partial premelting for a fast equilibration, scanning electron microscope investigations, annealing and quenching experiments, and X‐ray diffraction measurements are investigated based on the Fe–6W–5Mo–Cvar and Fe–10Cr–3W–Cvar system. The focus of the combined investigations is the determination of the high‐temperature phase transformations and the identification of the primary carbide type.